A Randomized Comparison Between Ultrasound- and Fluoroscopy-Guided C7 Medial Branch Block. Issue 1 (January 2015) - Finlayson, Roderick J.; Etheridge, John-Paul B.; Tiyaprasertkul, Worakamol; Nelems, Bill; Tran, De Q.H.
<x xml:space="preserve">Abstract</x> Background Because of its location in the lower neck and anatomical variability, the C7 medial branch represents a challenging target for local anesthetic blocks. Although ultrasound (US) guidance offers an alternative to fluoroscopy for C3 to C6 cervical medial branch blocks (CMBBs), its use at the C7 level has not been examined. We hypothesized that US, using a biplanar imaging technique, could provide a shorter performance time than conventional fluoroscopy for C7 CMBB. Methods Fifty patients undergoing C7 CMBB were randomized to fluoroscopy or US guidance. A 0.6-mL mixture of local anesthetic and radiographic contrast was injected in both groups. The primary outcome was performance time. Secondary outcomes included success rate, pain levels preblock and postblock, and incidences of aberrant spread and procedure-related complications. Results Compared to fluoroscopy, US guidance was associated with a shorter performance time (233.6 ± 80.4 vs 390.6 ± 142.4 seconds; P < 0.001) and fewer needle passes (2 vs 4; P < 0.001). However, both imaging modalities provided similar success rates (92%–96%). Furthermore, no intergroup differences were found in preblock and postblock pain scores. In the fluoroscopy group, intravascular and intra-articular spreads were seen in 20% and 4% of cases, respectively. In the US group, a blood vessel was visualized overlying the target area and successfully avoided during needle insertion in 40% of patients. No procedure-related complications occurred in either group. Conclusions Ultrasound guidance using a biplanar approach provides a similar success rate to fluoroscopy for C7 CMBB. However, US is associated with improved efficiency (decreased performance time and fewer needle passes).